Serologic Evidence for Hepatitis B Virus Infection in Patients with Hemophilia B - Hoofnagle, Jay H; Aronson, David; Roberts, Harold (Thrombosis and Haemostasis, 1975)
Among sera from 160 patients with hemophilia B from 9 centers in Europe and North and South America, 2.5% were positive for hepatitis B surface antigen (HBsAg), 60% for antibody to HBsAg, and 31% for antibody to the hepatitis B core antigen. Evidence of exposure to the hepatitis B virus appeared to be related to severity of disease and age rather than the source and method of manufacturer of factor IX concentrate.